DY Fuzzing: Formal Dolev-Yao Models Meet Cryptographic Protocol Fuzz Testing - Ammann, Max; Hirschi, Lucca; Kremer, Steve (Proceedings - IEEE Symposium on Security and Privacy, 2024)
Critical and widely used cryptographic protocols have repeatedly been found to contain flaws in their design and their implementation. A prominent class of such vulnerabilities is logical attacks, e.g. attacks that exploit flawed protocol logic. Automated formal verification methods, based on the Dolev-Yao (DY) attacker, formally define and excel at finding such flaws, but operate only on abstract specification models. Fully automated verification of existing protocol implementations is today still out of reach. This leaves open whether such implementations are secure. Unfortunately, this blind spot hides numerous attacks, such as recent logical attacks on widely used TLS implementations introduced by implementation bugs.We answer by proposing a novel and effective technique that we call DY model-guided fuzzing, which precludes logical attacks against protocol implementations. The main idea is to consider as possible test cases the set of abstract DY executions of the DY attacker, and use a novel mutation-based fuzzer to explore this set. The DY fuzzer concretizes each abstract execution to test it on the program under test. This approach enables reasoning at a more structural and security-related level of messages represented as formal terms (e.g. decrypt a message and re-encrypt it with a different key) as opposed to random bit-level modifications that are much less likely to produce relevant logical adversarial behaviors. We implement a full-fledged and modular DY protocol fuzzer. We demonstrate its effectiveness by fuzzing three popular TLS implementations, resulting in the discovery of four novel vulnerabilities.